(untitled) (Veterinary Science, 2017)
In this study the technical and economic feasibility of using ground sorghum grain in diets for breeding isoproteic to corral British breed calves tested. They were grouped by body weight and assigned to three treatments (T) based on grain sorghum (GS) with different protein sources for 80 days: Grain sorghum (57.96%) with Sunflower Pellet (G) (32, 04%) TI (GSG); Grain sorghum (67.95%) with Pellet soy (S) (22.05%) TII (GSS); Grain sorghum (3.87%) with wheat bran (A) (86.13%) TIII (GSA). The intake of dry matter (DM) had significant differences (P <0.027); the higher DM intake (7.16 kg. /d) was for TI (GSG). The daily weight gains were significantly different (P <0.0116) throughout the study for TI (GSG) and TIII (GSA) respectively. The cost ( / day / kg daily gain) treatment TIII (GSA) was lower than the other two treatments TI and TII GSG GSS. It was concluded that using grain sorghum isoproteic diets in rearing calves the best production results were achieved when mixed with pellet sunflower or soy as a protein source